AN ANALYSIS SAFETY AND HEALTH RISK WORK ON INSTALLATION HEALTH OFFICERS EMERGENCY IN HOSPITAL LEVEL IV. 01.07.02 BINJAI - Nurul Mutiah; Ermi Girsang; Sri Lestari Ramadhani Nasution (SEAN Institute, 2022)
K3RS are all activities to guarantee and protect the safety and health of hospital human resources, patients, patient companions, visitors, and the hospital environment through efforts to prevent work accidents and occupational diseases. In carrying out their duties, nurses experience health and safety problems. This study aims to analyze the health and safety risks of health workers in the emergency department (IGD) at the Kindergarten Hospital. IV. 01.07.02 Binjai and seek appropriate risk control for nurses to avoid work accidents and occupational diseases. The risk level assessment refers to the “William Fine” formula and table. It was concluded that the greatest level of hazard was obtained by stitching the wound with the risk of needle sticks, contracting HIV/AIDS, and cleaning the wound. Hospitals are advised to carry out further control efforts by the K3 control hierarchy.